2020
DOI: 10.3390/ijerph17249506
|View full text |Cite
|
Sign up to set email alerts
|

An Association between Rainy Days with Clinical Dengue Fever in Dhaka, Bangladesh: Findings from a Hospital Based Study

Abstract: Background: Dengue, a febrile illness, is caused by a Flavivirus transmitted by Aedes aegypti and Aedes albopictus mosquitoes. Climate influences the ecology of the vectors. We aimed to identify the influence of climatic variability on the occurrence of clinical dengue requiring hospitalization in Zone-5, a high incidence area of Dhaka City Corporation (DCC), Bangladesh. Methods and Findings: We retrospectively identified clinical dengue cases hospitalized from Zone-5 of DCC between 2005 and 2009. We extracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…The travel history of the patient was revealed as a significant risk factor for the dengue infection in this study as described by others (Verma et al 2014). A portion of our cases (n=57) visited the capital Dhaka which was the hotspot of outbreaks and circulate infection throughout the year (Rahman et al 2020). A study in India found that 70% of cases traveled to neighboring cities and expressed the signs of infection within the following 7 days (Swain et al 2020).…”
Section: Resultssupporting
confidence: 73%
“…The travel history of the patient was revealed as a significant risk factor for the dengue infection in this study as described by others (Verma et al 2014). A portion of our cases (n=57) visited the capital Dhaka which was the hotspot of outbreaks and circulate infection throughout the year (Rahman et al 2020). A study in India found that 70% of cases traveled to neighboring cities and expressed the signs of infection within the following 7 days (Swain et al 2020).…”
Section: Resultssupporting
confidence: 73%
“…The patient's travel history was revealed as a significant risk factor for the dengue infection in this study as described by others [ 23 ]. A portion of our cases (n = 57) visited the capital Dhaka which was the hotspot of outbreaks and circulated infection throughout the year [ 24 ]. A study in India found that 70% of cases traveled to neighboring cities and expressed the signs of infection within the following 7 days [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…When we evaluated the studies regarding the types of models used in the predictions, we observed that the vast majority of authors investigated moving average models (27), such as the Autoregressive Integrated Moving Average (ARIMA) (17,23,29,35,41,43,46,56,(61)(62)(63), Seasonal Autoregressive Integrated Moving Average (SARIMA) (55,(63)(64)(65)(66), Autoregressive Integrated Moving Average with Explanatory Variable (ARIMAX) (67). Several works have also presented a wide variety of models using artificial neural networks, mainly the LSTM (59,(68)(69)(70).…”
Section: Arboviruses (Counts) Predictionmentioning
confidence: 99%